Magic box – not only flesh but also with a fatal bone: A rare case of extraskeletal intra-abdominal osteogenic sarcoma (Indian Journal of Case Reports, 2021)
Extraskeletal osteogenic sarcoma is a rare tumor with a poor prognosis. It is histologically characterized by the formation of malignant osteoid, however, there is no association with the axial or appendicular skeleton. It comprises less than 2% of the soft-tissue sarcomas. Postulated risk factors for the development of extraskeletal osteogenic sarcoma are middle and elderly aged patients, history of radiation in the past, and trauma. Here, we report a rare case of extraskeletal intra-abdominal osteogenic sarcoma in a 56-year-old female who presented with a complaint of on and off abdominal pain for the past month. The patient presented with a large retroperitoneal soft-tissue mass with areas of calcifications on CT. Positron emission tomography-CT revealed a large mass with diffuse fluorodeoxyglucose uptake with no other lesion elsewhere in the body. A CT-guided tru-cut biopsy was taken and immunohistochemistry was done on the same. This was proven as osteogenic sarcoma on immunohistochemistry. The patient was started on palliative chemotherapy as the mass was not resectable.